The Adverse Impacts of Disasters In-Name-Only - Giovanni Baiocchetti; Cecilia Castaldo; Ilan Noy; Federico Zampollo (CESifo GmbH, 2025)
Disasters caused by natural hazards, such as earthquakes or hurricanes, have many adverse consequences associated with the physical damage they cause. Here, we show that the very name given to a disaster can also lead to adverse consequences. We argue that the name used for a disaster is significant, and is distinct from the physical event itself. Specifically, we show that the toponyms (place names) used to refer to disaster events by the media and the authorities have consequences if these toponyms do not accurately align with the disaster-affected region. Examples of inaccurate disaster toponyms abound, but the costs of these inaccurate toponyms have yet to be recognized. When a disaster damages area A and not area B, but the toponym adopted for that disaster encompasses both A and B, we show that B experiences a decline in tourism that is unrelated to the hazard event that hit only area A. We also show that once B's name has been tarnished, it becomes difficult to clear its name. Our examples are three recent Italian earthquakes for which we quantify the impact on tourism of the earthquakes themselves and of the toponyms they were given. Once an area is defined as affected, even when it was not, this designation leads to a statistically significant and economically material decline in tourism – in our examples, this amounts to an unnecessary 10-15 percent decline in tourist arrivals that endures for several years following the event. We finish by making some observations about how disasters should be named.
Keywords: Q54; R11; Z39; 330; earthquake; tourism; toponyms; media; panel match